Evidence for one-dimensional chiral edge states in a magnetic Weyl semimetal Co3Sn2S2 - Sean Howard (Nature Portfolio, 2021)
Magnetic Weyl semimetals in the 2D limit may behave like 2D Chern insulators and host the quantum anomalous Hall effect at high temperatures. Here, the authors report the observation of linearly dispersing topological states confined to the edges of the kagome Co3Sn terraces in the magnetic Weyl system Co3Sn2S2.